2017
DOI: 10.1039/c7ra10633e
|View full text |Cite
|
Sign up to set email alerts
|

Insights into energy-efficient and eco-friendly sealing of anodic aluminum oxide film holes with alkaline earth metal salts

Abstract: In this study, the impact of various sealing conditions on the quality of the sealed anodic aluminum oxide (AAO) film is systematically investigated, leading us to gain insights into sealing the AAO film in an energy-efficient and eco-friendly way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Since from the review of the mechanism(s) of the sealing process above it is quite obvious that some dissolution of the pore walls is necessary to generate materials of higher specific volume to fill the pores under the sealing conditions, appreciation of factors that might influence alumina dissolution and/or boehmite precipitation will be vital to developing new sealing procedures that enhance energy efficiency of the sealing process. Wei et al [19] had demonstrated that greatest influence on sealed film quality is exerted by temperature, followed by the pH of the sealing media, then the presence of salts, surfactants, and complexants, respectively, (i.e., temperature > pH > salt mixture > surfactant > complexant). Sheasby and Bancroft [159] had reported that pH drops in the hot water sealing bath below 5·5 (recommended pH 5.5 to 6.5) leads to inhibited formation of boehmite during sealing, and resultant poor sealing outcomes.…”
Section: Factors Affecting Sealing and How These Factors Might Be Expmentioning
confidence: 99%
See 1 more Smart Citation
“…Since from the review of the mechanism(s) of the sealing process above it is quite obvious that some dissolution of the pore walls is necessary to generate materials of higher specific volume to fill the pores under the sealing conditions, appreciation of factors that might influence alumina dissolution and/or boehmite precipitation will be vital to developing new sealing procedures that enhance energy efficiency of the sealing process. Wei et al [19] had demonstrated that greatest influence on sealed film quality is exerted by temperature, followed by the pH of the sealing media, then the presence of salts, surfactants, and complexants, respectively, (i.e., temperature > pH > salt mixture > surfactant > complexant). Sheasby and Bancroft [159] had reported that pH drops in the hot water sealing bath below 5·5 (recommended pH 5.5 to 6.5) leads to inhibited formation of boehmite during sealing, and resultant poor sealing outcomes.…”
Section: Factors Affecting Sealing and How These Factors Might Be Expmentioning
confidence: 99%
“…Furthermore, the applicability of another hitherto popular sealing process; chromate sealing, is currently limited to essential parts in the aerospace industry due to toxicological, health, and environmental implications traced to Cr(VI) employed in the process [7][8][9][10][11][12][13][14][15][16]. On the other hand, the advantages of another industrially utilized sealing process; the nickel fluoride (cold) sealing process is limited by the toxicity of nickel salts which narrows its range of application, and introduces added costs due to post-sealing wastewater treatments and management [17][18][19][20]. Further efforts at sealing anodized aluminum at temperatures lower than that used in hydrothermal (high temperature) sealing, have led to much variety in the chemical constitution and operating temperatures of sealing baths [21].…”
mentioning
confidence: 99%
“…Anodic aluminum oxidation processing and electrodeposition treatment can allow the aluminum alloy to bear different structural colors, providing exciting opportunities for bringing such materials to the fields of decorative materials [1417]. However, only a limited number of colors has been produced by the traditional coloration techniques [14,16,1819]. To widen the spectrum of colors, many researchers turn to mimic the structural color from nature, which is expected as the origin for the artificial creation of multiple and stable colors existing on the surface of aluminum alloys [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Two types of strategies have been employed to produce structural colors, one is based on self-assembly methods [24], and the other is based on electrodeposition [18]. The former involves the simultaneous assembly of the basic structural units such as molecules, nanomaterials, and the materials on the microscale or even larger scales to form an ordered structure.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Therefore, most researchers sealed the pore structure using corrosionresistant materials after anodization as a post-treatment to enhance the anticorrosion quality of porous AAO. 10,11 Zheng et al reported that chemical modification after anodizing could also increase the anticorrosion of aluminum alloys. 12 Sealing the pores on AAO is Commonly achieved by hydrothermal sealing.…”
Section: Introductionmentioning
confidence: 99%